Improving corrosion protection of urethane acrylate UV curable coatings derived from palm oil via graphene oxide particle incorporation - Mohd Sofian Alias,; Rabiahtul Zulkafli,; Norinsan Kamil Othman,; Mohd Suzeren Md. Jamil,; Siti Radiah Mohd Kamarudin,; Siti Fatahiyah Mohamad,; Mohd Hamzah Harun,; Mahathir Mohamed,; Maznah Mahmud, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores the enhancement of corrosion protection properties in urethane acrylate UV-curable coatings derived from palm oil through the incorporation of graphene oxide particles (GOP). GOP were added into palm oil-based urethane acrylate (POBUA) using a sonication technique. The performance of POBUA with the influence of GOP was determined using Thermal Gravimetric analysis (TGA) and Field Emission Scanning Electron Microscopy (FESEM). Meanwhile, the corrosion testing was confirmed by electrochemical testing of Electrochemical Impedance Spectroscopy (EIS). TGA demonstrated that the presence of GOP a coating additive, improved the coating in the POBUA, enabling better heat absorption. This is because more energy was required to break the polymer chain during decomposition. Additionally, EIS showed that the diffusion of corrosive ions was hindered due to the tortuous pathways created by the GOP within the POBUA network. The highest Rct value of POBUA coating with 0.5 wt% GOP give 99.64% corrosion protection for mild steel which significantly improved compared to neat POBUA coating which only 63.6% corrosion protection. Furthermore contact angle analysis showed the presence of GOP improved hydrophobicity properties of POBUA coating contributing to their excellent corrosion resistance. These findings highlight the potential of POBUA/GOP curable coatings for providing effective protection of mild steel surfaces.